KRAS variant allele frequency, but not mutation positivity, associates with survival of patients with pancreatic cancer. Issue 9 (12th June 2022) - Suzuki, Tatsunori; Masugi, Yohei; Inoue, Yosuke; Hamada, Tsuyoshi; Tanaka, Mariko; Takamatsu, Manabu; Arita, Junichi; Kato, Tomotaka; Kawaguchi, Yoshikuni; Kunita, Akiko; Nakai, Yousuke; Nakano, Yutaka; et al.
Abstract: KRAS mutation is a major driver of pancreatic carcinogenesis and will likely be a therapeutic target. Due to lack of sensitive assays for clinical samples of pancreatic cancer with low cellularity, KRAS mutations and their prognostic association have not been fully examined in large populations. In a multi‐institutional cohort of 1162 pancreatic cancer patients with formalin‐fixed paraffin‐embedded tumor samples, we undertook droplet digital PCR (ddPCR) for KRAS codons 12/13/61. We examined detection rates of KRAS mutations by clinicopathological parameters and survival associations of KRAS mutation status. Multivariable hazard ratios (HRs) and 95% confidence intervals (CIs) for disease‐free survival (DFS) and overall survival (OS) were computed using the Cox regression model with adjustment for potential confounders. KRAS mutations were detected in 1139 (98%) patients. The detection rate did not differ by age of tissue blocks, tumor cellularity, or receipt of neoadjuvant chemotherapy. KRAS mutations were not associated with DFS or OS (multivariable HR comparing KRAS ‐mutant to KRAS ‐wild‐type tumors, 1.04 [95% CI, 0.62–1.75] and 1.05 [95% CI, 0.60–1.84], respectively). Among KRAS ‐mutant tumors, KRAS variant allele frequency (VAF) was inversely associated with DFS and OS with HRs per 20% VAF increase of 1.27 (95% CI, 1.13–1.42; p trend  <0.001) and 1.31 (95% CI, 1.16–1.48; p trend  <0.001), respectively. In summary, ddPCR detected KRAS mutations in clinical specimens of pancreatic cancer with high sensitivity irrespective of parameters potentially affecting mutation detections. KRAS VAF, but not mutation positivity, was associated with survival of pancreatic cancer patients. Abstract : Droplet digital PCR provides highly sensitive mutation calling in clinical tumor samples irrespective of quality and quantity of tumor DNA. KRAS variant allele frequency, but not mutation positivity, can be a prognostic biomarker in pancreatic cancer.